Age determines the risk of familial inflammatory bowel disease—A nationwide study. Issue 3 (22nd April 2022) - Halfvarson, Jonas; Ludvigsson, Jonas F.; Bresso, Francesca; Askling, Johan; Sachs, Michael C.; Olén, Ola
Summary: Background and Aims: To estimate familial aggregation of inflammatory bowel disease (IBD), we performed a nationwide, case–control study and examined the odds for patients with IBD (vs controls) to have a first‐degree relative (FDR) with IBD, by age of diagnosis, type of family history and IBD subtype. To assess the incidence of future IBD in relatives of incident IBD patients, we performed a cohort study. Methods: Individuals diagnosed with IBD ( N  = 50, 667) between 2003 and 2017 with at least one FDR were identified from Swedish national registers and compared to general population controls ( N  = 506, 720) with at least one FDR. We used logistic regression to calculate adjusted odds ratios (ORs) and Cox regression to estimate hazard ratios (HRs). Results: Compared to controls, IBD cases more often had a mother (3.0% vs 0.9%, OR = 3.5; 95% CI: 3.3–3.7), father (2.9% vs 0.8%, OR = 3.5; 95% CI: 3.3–3.7), full sibling (5.3% vs 1.5%, OR = 3.6; 95% CI: 3.4–3.8) and child (2.4% vs 0.9%, OR = 2.6; 95% CI: 2.4–2.8) with IBD. The strength of association increased with the number of affected FDRs and was modified by subtype of IBD and age of diagnosis. Highest ORs were observed for paediatric IBD among paediatric‐onset Crohn's disease (OR = 10.6; 95% CI: 8.2–13.5) and paediatric‐onset ulcerative colitis (OR = 8.4; 95% CI: 6.4–10.9) cases. The 10‐year cumulative incidence of IBD was 1.7% in full‐siblings of incident IBD patients vs 0.4% among full‐siblings of reference individuals. Conclusion: The variations in the strength of familial IBD and future risk of IBD in FDRs support differences in genetic predisposition and call for targeted approaches in potential screening programmes. Abstract : The association between IBD cases and FDRs with IBD differed by age of IBD diagnosis in both index cases and FDRs. For all IBD subtypes, the highest ORs were observed for childhood‐onset IBD in both cases and FDRs and the lowest for elderly‐onset IBD in both index cases and FDRs.